Deformed N=8 supergravity from IIA strings and its Chern‐Simons duals. Issue 4 (22nd December 2015) - Guarino, Adolfo; Jafferis, Daniel L.; Varela, Oscar
Abstract : Do electric/magnetic deformations of N = 8 supergravity enjoy a string/M‐theory origin, or are they just a four‐dimensional artefact? We address this question for the gauging of a group closely related to SO ( 8 ) : its contraction ISO ( 7 ) . We argue that the deformed ISO ( 7 ) supergravity arises from consistent truncation of massive IIA supergravity on S 6, and its electric/magnetic deformation parameter descends directly from the Romans mass. The critical points of the supergravity uplift to AdS4 massive type IIA vacua and the corresponding CFT3 duals are identified as super‐Chern‐Simons‐matter theories with gauge group SU ( N ) and level k given also by the Romans mass.